The Empirical Examination of Different Customer Types - Tamás, K.; Kiss, Virág Ágnes (International Journal of Engineering and Management Sciences, 2018)
The proper knowledge of customer types is essential for a well functioning company – regardless of its size. In current research we wanted to identify and characterize the particular customer groups with involving 302 persons. During the examination we measured the attitudes of these participants with the help of a statement range based on Kotler’s classical customer types. For the identification we made factor- and cluster analysis, and we could separate five different factors. They received the names of Angry, Definite, Discursive Passive, Experience Shopping and Indefinite - based on some related statements. After the cluster analysis – along these factors - we could separate four different groups: Young Impulse Shoppers, Outspoken Definites, Negatives and Born Customers. Each and every group requires different communication, sales attitude and service morals.